Unearthing Al-Dirah's authentic charm: a case study for city branding in Riyadh - Yenny Rahmayati; Haya Alshammari; Razan Alomar; Taif Almarshad; Najla Alzahrani; Amjad Alqubaily (Journal of City: Branding and Authenticity, 2023)
Al-Dirah, an old neighborhood in Riyadh, is an excellent illustration of Saudi tradition and history. It was built in 1824 and is widely known for its rich heritage and historical traits, with historic landmarks such as Al Masmak Fort, Al-Dirah Souk, Al-Mu'eiqilia Market, and Deera Square. It also had the major royal castle in Saudi Arabia's second state. It was a thriving economic neighborhood from the past until the present times. With all these values, Al-Dirah has the potential to represent the branding of Riyadh as the capital city. However, this district is facing challenges such as traffic, overpopulation, collapsing buildings, and maintenance issues which might impact the image of the neighborhood. This study aims to investigate the values and potentials of the Al-Dirah neighborhood as well as recent urban problems from the perspectives of residents and non-residents. It argues that having significant potential ranging from cultural, historical, and economic is not enough for developing the branding for the city without considering the perceptions of the residents. Their perceptions are important to create an image that can be potential for the city branding. Therefore, their role needs to be recognized. A mixed method both qualitative and quantitative approach was utilized for this study through online structured and open-ended questionnaires, supported by direct observations on the site. The findings reveal that although old neighborhoods are often associated with urban problems and poorly built environments, however, from residents’ perspectives, it has the potential for city branding, especially if it is supported by their cultural, historical, and economic values. While most of the studies related to city branding focus on the policies perspective from the top-down, this study gives another perspective which is from the community or bottom-up. This study supports the Saudi Vision 2030 goals to achieve a sustainable living environment, boost the economy through tourism, and strengthen national identity at the same time. This study enriches references about city branding for practitioners and policymakers.